Characteristics of the Wolf (Canis lupus labradorius Goldman) in Northern Quebec and Labrador - Parker, G.R.; Luttich, S. (ARCTIC, 1986)
Two hundred and twelve wolves (Canis lupus labradorius) shot by hunters in northern Quebec and Labrador during the winters of 1976-77 through 1983-84 were examined for various population parameters. An estimated annual adult survival rate of 55% and a recruitment rate of 49% suggest a population of moderate exploitation. The sex ratio did not differ significantly from 1:1. Fifty-five percent of yearling females were pregnant or in breeding condition. The average litter size for all females was 6.8. Internal fat deposits were greatest in young males and older females. Caribou (Rangifer tarandus caribou) was the most common food item found in stomachs. A sample of caribou killed by wolves in the winter showed a selection for older-aged caribou with fat deposits slightly below that of the general population.Key words: wolf, caribou, northern Quebec, Labrador, predation Mots clés: loup, caribou, nord du Québec, Labrador, activité prédatrice